Awareness and Perceptions of Palliative Care Among the Elderly: A Qualitative Study. Issue 2 (April 2022) - Lei, Lei; Lu, Ya; Gan, Quanxi; Hu, Zongping; Luo, Yu
Objectives : With the rapidly aging population worldwide, the demand for palliative care is increasing. Palliative care publicity and education must be further developed globally, especially for the elderly. It is essential to perform targeted promotion by understanding the awareness and needs of palliative care of the elderly. This study aimed to investigate elderly people's awareness of palliative care and their own views on and needs for palliative care, which could provide a basis for the popularization of palliative care among them.Methods : A total of 20 elderly people were recruited to participate in the semi-structured, and in-depth interviews. Participants were from communities and nursing homes in Chongqing, China. The interview transcripts were coded using the method of thematic analysis.Results : Finally, 4 themes and 10 subthemes were identified, that is: unawareness of the concept of palliative care (never heard of palliative care, confusion between euthanasia and palliative care), motivations for accepting palliative care (personal perspective: less suffering; family perspective: relieving the burden), factors influencing palliative care decision (cost of palliative care, knowledge of palliative care, opinion of decision-making agents), and necessity and preferences for publicizing palliative care (eagerness to know more about palliative care, focusing on policy and charges, preference for Electronic Media Advertising).Conclusions : Palliative care publicity among the elderly is important and necessary. Findings in this study could provide some insights into how to popularize palliative care among the elderly. Considering the preference of the elderly for access to palliative care information, simultaneous publicity through TV and online channels is suggested. Since the elderly would like to choose their doctors and adult children as decision-making agents, more communication between community, health professionals and family is advocated.